2012
DOI: 10.1074/jbc.m111.309468
|View full text |Cite
|
Sign up to set email alerts
|

Human Mitochondrial DNA Helicase TWINKLE Is Both an Unwinding and Annealing Helicase

Abstract: Background: TWINKLE is the human mitochondrial DNA helicase associated with heritable neuromuscular diseases. Results: TWINKLE has NTPase-dependent DNA unwinding activity and NTPase-independent DNA annealing activity. The unwinding activity is enhanced by displaced strand traps. Conclusion: TWINKLE has more than one ssDNA-binding sites, the one associated with annealing interferes with unwinding in the absence of traps. Significance: The annealing activity may be involved in recombination-mediated replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
90
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 37 publications
3
90
0
Order By: Relevance
“…When ATP is added, ϳ17 and 8% of the molecules display clear unwinding/reannealing and unwinding events, respectively. These results are consistent with a previous bulk study that showed Twinkle annealing activity can take place in the presence of a non-hydrolyzable nucleotide analogue or in the absence of nucleotide, but rates of annealing increased when a hydrolyzable nucleotide was added (12).…”
Section: Twinkle Unwinding and Binding Activity On Replicationsupporting
confidence: 82%
See 4 more Smart Citations
“…When ATP is added, ϳ17 and 8% of the molecules display clear unwinding/reannealing and unwinding events, respectively. These results are consistent with a previous bulk study that showed Twinkle annealing activity can take place in the presence of a non-hydrolyzable nucleotide analogue or in the absence of nucleotide, but rates of annealing increased when a hydrolyzable nucleotide was added (12).…”
Section: Twinkle Unwinding and Binding Activity On Replicationsupporting
confidence: 82%
“…Here we observed that Twinkle unwound the 5Ј tailed duplex substrate (substrate 5) at ϳ5-fold greater rate than the 3Ј tailed duplex (substrate 6) (Fig. 3B), consistent with its preferential 5Ј to 3Ј directionality of unwinding under multi-turnover conditions (10,12).…”
Section: Twinkle Unwinding and Binding Activity On Replicationsupporting
confidence: 60%
See 3 more Smart Citations